Pelaksanaan Sistem Uji Kendaraan Bermotor dalam Mencegah Kecelakaan Lalu Lintas di Kota Denpasar - I Wayan Ary Setiawan; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
The road traffic and transportation system has a strategic role as a means of facilitating the flow of goods and services transportation. In carrying out the implementation of traffic rules, all levels of society must pay attention to the safety of the community on the highway, as well as the achievement of welfare. How is the implementation of the motor vehicle testing system in the motor vehicle testing unit?, and How is the effectiveness of the motor vehicle testing system regulations and the obstacles faced in preventing traffic accidents in Denpasar City?. The empirical method was chosen to conduct this research, by interviewing the informants directly is one of the empirical methods used. By interviewing resource persons who are experts in the motor vehicle test system to ensure passenger safety and minimize road accidents. The results of the study indicate that the implementation of the motor vehicle testing system in the motor vehicle testing unit based on Law Number 22 of 2009 concerning Road Traffic and Transportation related to Article 49 concerning Motorized Vehicle Testing is still not effective in its implementation.